2017
DOI: 10.1089/dna.2017.3656
|View full text |Cite
|
Sign up to set email alerts
|

miR-144-3p Induces Cell Cycle Arrest and Apoptosis in Pancreatic Cancer Cells by Targeting Proline-Rich Protein 11 Expression via the Mitogen-Activated Protein Kinase Signaling Pathway

Abstract: microRNAs (miRNAs) have been proved to be involved in many events of tumor development and progression, including cell proliferation, cell apoptosis, and cell cycle arrest. However, the potential role of miR-144-3p in pancreatic cancer (PC) remains elusive. In this study, we demonstrated that miR-144-3p was decreased in PC tissues and PANC-1 cells, whereas proline-rich protein 11 (PRR11) was remarkably increased. miR-144-3p mimics were discovered to inhibit cell proliferation by arresting cells at the S-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…Blue dots indicate congregation of the control group, and red dots indicate congregation of the depression group with mental disorders. 47 miR-144-3p-targeted genes includes Wnt/β-catenin, Nrf2 and MAKP signalling pathways, [48][49][50] which have been verified in the physiology of depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blue dots indicate congregation of the control group, and red dots indicate congregation of the depression group with mental disorders. 47 miR-144-3p-targeted genes includes Wnt/β-catenin, Nrf2 and MAKP signalling pathways, [48][49][50] which have been verified in the physiology of depression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR‐144‐3p can regulate ataxin 1 (ATXN1) mRNA expression in human cells, and a search of the Genetic Association Database shows that ATXN1 is associated with mental disorders . miR‐144‐3p‐targeted genes includes Wnt/β‐catenin, Nrf2 and MAKP signalling pathways, which have been verified in the physiology of depression.…”
Section: Discussionmentioning
confidence: 99%
“…PRR11 was is a newly identified oncogene, which could promote the proliferation of PC cells. 18 Therefore, we aimed to explore whether downregulation of USP34 could inhibit the proliferation of PANC-1 cells via regulating the expression of PRR11. As shown in Figure 2A, the level of PRR11 was obviously upregulated in PANC-1 cells following infection with lenti-PRR11.…”
Section: Downregulation Of Usp34 Inhibited the Proliferation Of Pc Cementioning
confidence: 99%
“…Various studies have reported miR‐144‐3p to be an important regulator for apoptosis . A recent study shows that miR‐144‐3p expression is dysregulated in the brain with traumatic brain injury .…”
Section: Introductionmentioning
confidence: 99%